Socio-economic rights in South Africa : symbols or substance? / edited by Malcolm Langford [and three others]. - Langford, Malcolm (Cambridge University Press, 2014)
The embrace of socio-economic rights in South Africa has featured prominently in scholarship on constitution making, legal jurisprudence and social mobilisation. But the development has attracted critics who claim that this turn to rights has not generated social transformation in practice. This book sets out to assess one part of the puzzle and asks what has been the role and impact of socio-economic strategies used by civil society actors. Focusing on a range of socio-economic rights and national trends in law and political economy, the book's authors show how socio-economic rights have influenced the development of civil society discourse and action. The evidence suggests that some strategies have achieved material and political impact but this is conditional on the nature of the claim, degree of mobilisation and alliance building, and underlying constraints.